Blueberry Gardener’s Guide - Jeffrey G. Williamson; Paul M. Lyrene; James W. Olmstead (EDIS)
Home gardeners: Use this guide to successfully grow blueberries in Florida. This revised 8-page fact sheet was written by J.G. Williamson, P.M. Lyrene, and J.W. Olmstead, and published by the UF Department of Horticultural Sciences, January 2012.